Social Factors Related to Sexual Satisfaction Between Couples (Case Study: Citizens of Tabriz City) - Fattaneh Hajilou; Fatemeh Golabi; Bahman RanjegarGalekandy (توسعه اجتماعی)
Sexual satisfaction is an important factor effect on marital satisfaction. This research was conducted to investigate social factors related to sexual satisfaction among married people in Tabriz City. The current research is a cross-sectional survey. The target population is married people living in three urban areas of the ten districts of Tabriz city in 2022. The sample size is 384 people were determined based on Cochran's formula and the volunteers participating in the research were investigated using the stratified random sampling method. Descriptive statistics methods were used to describe the data and independent t-tests, analysis of variance, and Pearson's correlation test were used in SPSS software version 22 to check the relationship between variables. Demographic variables have also shown a significant effect on the variable of sexual satisfaction. The results of the research show that homo spouse is one of the social factors influencing the sexual satisfaction of couples. Also, other findings of the research show that education, income, age of the couple, and number of children are factors influencing the sexual satisfaction of couples.